Periodesasi Pendidikan Islam pada Masa Rasulullah SAW Ahd Al Makkiy dan Ahd Al Madaniyy - Radhinal Abdullah; Tri Abdi Syahputra; Fatma Yulia (Departement of Mathematics Education, 2024)
The periodization of Islamic education during the time of Rasulullah SAW shows a significant evolution from individual and closed education to a more organized and inclusive education system. This research aims to examine the periodization of Islamic education during the time of the Prophet Muhammad. This research aims to understand the contribution and impact of various phases of education on the development of Muslims during that time. This research uses qualitative methods with a historical approach. Data was collected through in-depth literature studies of primary sources such as the Al-Qur'an and Hadith, as well as secondary sources including Islamic history books and relevant academic works. Data analysis was carried out using a descriptive-analytical approach to identify and describe the periodization and main characteristics of Islamic education in each phase of the life of the Prophet Muhammad. The periodization of Islamic education during the time of the Prophet Muhammad can be divided into several main phases. Makkan education was individualized and private, with a focus on teaching the basic principles of Islam to family and close friends. Learning was carried out in secret to avoid pressure and oppression from the Quraysh. Early Medina education After moving to Medina, Islamic education underwent a significant transformation with the establishment of institutions such as the Nabawi Mosque which became a center for education and social activities. Education began to involve the wider community, with a focus on the formation of a civilized and civilized society.